Peran Mediasi Keterlibatan Kerja Dalam Hubungan Antara Transformasi Kepemimpinan, Pertukaran Anggota Leader, dan Kinerja Pekerjaan - Kuswady, Dody; Hendarsjah, Hidajat (School of Business, Bogor Agricultural University (SB-IPB), 2022)
This research aims to find out the effect of transformational leadership and leader-member exchange on the job performance of employees in textile and garment manufacturing companies. This research is expected to be useful to inspire managers to prepare good steps and strategies to improve employee job performance and develop employees. The research was conducted on employees of textile and garment manufacture with a sample of 337 people. The research method uses regression test and analysis of the mediation of Baron and Kenny. The results of the study show that the job performance variable is not influenced by transformational leadership and is influenced by the leader-member exchange. The leader-member exchange variable is influenced by the transformational leadership variable. Work engagement variable is influenced by transformational leadership and not influenced by leader-member exchange. Work engagement mediating variable is as a mediator of transformational leadership relationship to job performance and not as a mediator of leader-member exchange relationship to job performance. Keywords: job performance, leader-member exchange, manufacture textile, transformational leadership, work engagment